Balancing bank profits and nonperforming loans: a multiple objective programming approach - Boubaker, Sabri; Le, Tu D. Q.; Manita, Riadh; Ngo, Thanh (Annals of operations research, 2025)
The recent operations research literature has witnessed an increasing trend of studies on banking efficiency, whereas nonperforming loans (NPLs) are often treated as undesirable output. A trending approach is to decompose the bank production into different processes or departments in charge of different inputs and outputs under the so-called network data envelopment analysis, in which a loan production department oversees both good and bad loans. This paper proposes a novel way to decompose the bank into two departments: one oversees profit maximization, and the other monitors NPLs minimization, making the bank’s main function multiple objective programming (MOP). We applied a MOP approach to examine the departmental and overall performance of 30 Vietnamese banks during 2019‒2021 and understand the factors that influence their performance. We found that the banks had their profit maximization performance improved. Still, NPLs minimization performance deteriorated during the examined period, indicating that the bad loans issue remains a threat to the industry. As such, balancing profits and NPLs is increasingly important for Vietnamese banks, with a focus on their risk management i.e., regarding the NPLs.